Variations in fatty acid and amino acid profiles of doi and rasomalai made from buffalo milk - Abu Hena Md. Asif; Gautam Kumar Deb; Md. Rezwanul Habib; Md. Harun-ur-Rashid; Md. Abid Hasan Sarker; Umma Fatema Shahjadee; Sharmin Akter Lisa; Salma Ahmed; Dag Ekeberg; Einar Vargas-Bello-Perez; Mohammad Ashiqul Islam (Journal of Advanced Veterinary and Animal Research, 2021)
Objective: This study investigated and compared the chemical composition, cholesterol content, fatty acid (FA), and amino acid (AA) profiles of doi and rasomalai made from buffalo milk. Materials and Methods: Bangladesh Agricultural University Dairy Farm, Mymensingh-2202, Bangladesh was the source of raw buffalo milk. Then, doi and rasomalai were produced and ana¬lyzed. Prior to the production of doi and rasomalai, the gross composition and AAs of milk were evaluated. Milk and dairy products were evaluated for gross composition using an automated milk analyzer and the Association of Agricultural Chemists techniques, respectively. At the Bangladesh Council for Scientific and Industrial Research, Dhaka, Bangladesh, the cholesterol, FA, and AA lev¬els of doi and rasomalai were determined. Additionally, atherogenic and thrombogenic indices were determined using established equations. Results: The results indicated that the majority of the proximate components were significantly greater (p < 0.05) in rasomalai than in doi. Rasomalai had 3.64 mg more cholesterol (p > 0.05) than doi. The FA profile was identical across doi and rasomalai with the exception of oleic acid (C18:1cis-9), which was 1.50% greater (p < 0.05) in rasomalai. The atherogenicity index was found to be statistically higher in doi than in rasomalai (p > 0.05). Similarly, the thrombogenic index was found to be significantly higher (p > 0.05) in doi (1.98) when compared to the rasomalai (1.92). The concentrations of all AAs were found to be quantitatively higher in doi than in rasomalai (p > 0.05). Conclusion: The conclusion is that buffalo milk rasomalai appears to have a higher nutritional density than buffalo milk doi. [J Adv Vet Anim Res 2021; 8(3.000): 511-520]